Synthesis and Characterization of Five, Sevene Heterocyclic Membered Rings (Baghdad Science Journal, 2025)
New compounds containing heterocyclic units have been synthesized. These compounds include 2-amino 5- phenyl-1,3,4-thiadiazole (1) as starting material to prepare the Schiff bases 2N[3-nitrobenzylidene -2 hydroxy benzylidene and 4-N,N-dimethyl aminobenzylidene] -5-phenyl-1,3,4-thiadiazole (2abc) , 2N[3-nitrophenyl, 2-hydroxyphenyl or 4-N,N-dimethylaminophenyl] 3-]2-amino-5-phenyl-1,3,4-thiadiazole]-2,3-dihydro-[1,3]oxazepine-benzo-4,7-dione] (3abc), 2N[3-nitrophenyl,2-hydroxyphenyl,4-N,N-dimethylaminophenyl]-3-[2-amino-5-phenyl-1,3,4-thiadiazole-2-yl]-2,3-dihydro-[1,3]oxazepine-4,7-dione[(4abc), 2-N-[3-nitrophenyl, 2-hydroxyphenyl or 4-N,N-dimethylaminophenyl]-3-[2-amino-5-phenyl-1,3,4-thiadiazole-2yl]-1,2,3-trihydro-benzo-[1,2-e][1,3] diazepine-4,7-dione (5abc) ,2N[2-(3-nitrophenyl,2-hydroxyphenyl or 4-N,N-dimethylaminophenyl)]-4-oxo-1,3-thiazolidine-3-yl]-2-amino-5-phenyl-1,3,4-thiadiazole (6abc), 2-N-[5-(3-nitrophenyl,2-hydroxyphenyl or 4-N,N-dimethylaminophenyl)-tetrazolo-1-yl]-2-amino-5-phenyl-1,3,4-thiadiazole (7abc) , 2-N-[5-(3-nitrophenyl,2-hydroxyphenyl or 4-N,N-dimethylaminophenyl)-3-[2-amino-5-phenyl-1,3,4-thiadiazole-2-yl]-2,3-dihydro-[1,3]oxazepine-benzo-4,7-dithione (8abc) , 2-N-[5-(3-nitrophenyl,2-hydroxyphenyl or 4-N,N-dimethylaminophenyl)-3-[2-amino-5-phenyl-1,3,4-thiadiazole-2-yl]-2,3-dihydro-[1,3]oxazepine -4,7-dithione -5-ene (9abc) and 2-N-[5-(3-nitrophenyl,2-hydroxyphenyl or 4-N,N-dimethylaminophenyl)-3-[2-amino-5-phenyl-1,3,4-thiadiazole-2-yl] -1,2,3-trihydro-benzo-[1,2-e][1,3] diazepine -4,7-dithione - (10abc) . the structures of these compounds were characterized by FT-IR, 1H,13C-NMR,Uv/vis spectroscopy and the melting points were determined besides the evaluation of its biological activity.